Targeting Metabolism to Induce Cell Death in Cancer Cells and Cancer Stem Cells - Claire Pecqueur; Lisa Oliver; Kristell Oizel; Lisenn Lalier; François M. Vallette (International Journal of Cell Biology)
Abnormal metabolism and the evasion of apoptosis are considered hallmarks of cancers. Accumulating evidence shows that cancer stem cells are key drivers of tumor formation, progression, and recurrence. A successful therapy must therefore eliminate these cells known to be highly resistant to apoptosis. In this paper, we describe the metabolic changes as well as the mechanisms of resistance to apoptosis occurring in cancer cells and cancer stem cells, underlying the connection between these two processes.